Assessment and Management of Professionalism Issues in Pathology Residency Training: Results From Surveys and a Workshop by the Graduate Medical Education Committee of the College of American Pathologists. (6th July 2015) - Domen, Ronald E.; Talbert, Michael L.; Johnson, Kristen; Post, Miriam D.; Brissette, Mark D.; Conran, Richard Michael; Hoffman, Robert D.; McCloskey, Cindy B.; Raciti, Patricia M.; Roberts, Cory Anthony; Rojiani, Amyn M.; Tucker, J. Allan; et al.
Professionalism issues are common in residency training and can be very difficult to recognize and manage. Almost one-third of the milestones for pathology recently instituted by the Accreditation Council for Graduate Medical Education encompass aspects of professionalism. Program directors are often unsure of how and when to remediate residents for unprofessional behavior. We used a case-based educational approach in a workshop setting to assist program directors in the management of unprofessional behavior in residents. Eight case scenarios highlighting various aspects of unprofessional behavior by pathology residents were developed and presented in an open workshop forum at the annual pathology program director's meeting. Prior to the workshop, 2 surveys were conducted: (1) to collect data on program directors' experience with identifying, assessing, and managing unprofessional behavior in their residents and (2) to get feedback from workshop registrants on how they would manage each of the 8 case scenarios. A wide range of unprofessional behaviors have been observed by pathology program directors. Although there is occasionally general agreement on how to manage specific behaviors, there remains wide variation in how to manage many of the presented unprofessional behaviors. Remediation for unprofessional behavior in pathology residents remains a difficult and challenging process. Additional education and research in this area are warranted.